Effectivenes of inoculation in alfalfa breeding in ecological conditions of the Bjelovar and Bilogora county - Darko Uher; Sulejman Redžepović; Mihaela Blažinkov; Dubravko Maćešić; Josip Čolo; Zvonimir Štafa; Sanja Sikora (Mljekarstvo)
Development and basic existence of animal production as well as production of high quality milk depends upon possibility of sufficient production of quality and protein sufficient forage. Forage crop that satisfies these demands is alfalfa which is one of the most important perennial forage crop legumes. The aim of this study was to enhance alfalfa production on acid soil by liming and alfalfa seed inoculation with efficient Sinorhizobium meliloti strains in order to reduce the use of mineral nitrogen fertilization and enable qualitative and cost effective production of forage on the dairy farms. Field trial was established at family farm in the area of Bjelovar and Bilogora county. During two years experimental period statistically significant influence of inoculation and liming on forage and dry matteryield was determined. Significantly the lowest yields were determined on untreated plots without liming material. In all untreated plots, significantly lower yields were determined, but significant differences in yields were also obtained by inoculation with different S. meliloti strains, emphasizing the importance of strains selection used for alfalfa inoculation. In both experimental years total forage yield were ranging from 34 t/ha (untreated plots without liming) up to 60 t/ha on plots inoculated with strain 2011 and without liming. Values of total dry matter yield for both experimental years ranged from 6.5 t/ha (untreated plots without liming) up to 15,7 t/ha on plots inoculated with strain 2011 without liming. Results of this study showed that application of liming materials for acidity removal had positive effect on alfalfa yields in both experimental years and significantly improved alfalfa production on acid soils. The results of this study clearly showed that inoculation with selected S. meliloti strains may improve alfalfa production on acid soils and may contribute to more efficient forage production for dairy farms under particular agroecological conditions.